2018
DOI: 10.1101/331249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleus- and plastid-targeted annexin 5 promotes reproductive development in Arabidopsis and is essential for pollen and embryo formation

Abstract: 4 8 Background 4 9 7 2of ANN5 is to orchestrate the plastidial and nuclear genome activities via protein-7 3 protein interactions however not only in maturing pollen but also during the transition 7 4 from the vegetative to the generative growth and embryo development. 7 5 7 6

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…Annexin genes have been reported to play significant roles in plant growth, development, and overcoming abiotic adversity [27][28][29][30][31][32][33][34][35][36][37]. Numerous annexin family gene members have been identified in other plants.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin genes have been reported to play significant roles in plant growth, development, and overcoming abiotic adversity [27][28][29][30][31][32][33][34][35][36][37]. Numerous annexin family gene members have been identified in other plants.…”
Section: Discussionmentioning
confidence: 99%
“…pLAT52:ANN5-YFP and pLAT52:ANN1-YFP transformants were generated in Arabidopsis Col-0 background. ANN5 RNAi-silenced lines 13 and 15 were previously generated in our lab (Lichocka et al, 2018). Arabidopsis plants were grown in Jiffy7 pots in controlled-environment chambers (Percival Scientific, Iowa, USA) at 22°C, ca.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to ANN1 , which is constitutively expressed in vegetative tissues and also during pollen development, the onset of ANN5 expression occurs in the bicellular microspore and its transcripts accumulate until the pollen maturity (Honys and Twell, 2004; Zhu et al, 2014b). Previous studies showed that downregulation of ANN5 level compromised pollen viability and vigor reflected by collapsing of the pollen grains and formation of the smaller grains with a reduced competitiveness compared to the wild-type grains (Zhu et al, 2014b; Lichocka et al, 2018). It was also shown that ANN5 in vitro binds to liposomes composed of phosphatidyl cholines and phosphatidyl serines in a calcium-dependent manner (Zhu et al, 2014a).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Arabidopsis thaliana (Arabidopsis), the nuclear gene RAB GTPASE HOMOLOG 8D (RAB8D, also called RABE1B) encodes a plastid-targeted counterpart of the prokaryotic translation elongation factor thermal unstable (EF-Tu), and is constitutively expressed in both shoots and roots (Lichocka et al, 2018;Liu et al, 2019). In prokaryotes, EF-Tu functions in translation through transporting aminoacyl-tRNA to the A site of the 70S ribosome.…”
Section: Introductionmentioning
confidence: 99%